Hot deformation, corrosion and oxidation behaviour of TiNbTaVW and CrNbTaVW refractory high entropy alloys for high-temperature applications - Bamisaye, Olufemi Sylvester (University of the Witwatersrand, Johannesburg, 2024)
The world’s technological growth and development drive a persistent demand for new class of materials with excellent mechanical properties that surpass those of existing commercial materials used in high temperature structural applications. In search of this new class of material, refractory high entropy alloys (RHEAs), which comprise high-melting-point refractory elements are considered by researchers. In this study, two RHEAs (TiNbTaVW and CrNbTaVW) were developed and their structural, mechanical and performance properties were evaluated. The RHEAs were compared with commercial grade IN718 alloy. Thermo-Calc software with SSOL4 database was used to determine the phases present and the volume of the phases. Empirical calculations were also used to predict the phases and stability of the RHEAs. Thermo-Calc and empirical calculations accurately predicted the solid solution phases in the TiNbTaVW and CrNbTaVW. The RHEAs were produced by vacuum arc melting. The TiNbTaVW RHEA comprise of dendritic BCC solid solution structure, while the CrNbTaVW RHEA comprise dendritic structure with multiphases (BCC1, BCC2, and Cr(VNb)2 C15- Laves). The TiNbTaVW and CrNbTaVW has higher hardness of 522±10 HV and 688±21 HV than the commercial IN718 alloy with 301±14 HV. The higher hardness of the RHEAs was attributed to the solid solution strengthening mechanism and second phase strengthening. The corrosion behaviour of TiNbTaVW and CrNbTaVW was compared with the commercial IN718 alloy in 3.5 wt% NaCl solution and 1M H2SO4 solution. The TiNbTaVW and CrNbTaVW had superior corrosion resistance as compared to commercial IN718 alloy in both 3.5 wt.% NaCl and 1M H2SO4 solutions. The corrosion rate of CrNbTaVW RHEA is lower than the TiNbTaVW RHEA and IN718 alloy in both 3.5 wt.% NaCl and 1M H2SO4 solutions. The oxidation behaviour of TiNbTaVW and CrNbTaVW were compared with the commercial IN718 alloy at 850°C and 1050°C for 15h. The IN718 has a superior oxidation resistance at 850°C and 1050°C than the TiNbTaVW and CrNbTaVW RHEAs. The hot deformation test was conducted only on the TiNbTaVW and IN718 because the CrNbTaVW disintegrated during loading at the jaws of the Gleeble machine. This disintegration could be attributed to stress concentrations that exist between the two BCC phases and the Cr(VNb)2 Laves phase during loading. The TiNbTaVW and IN718 flow curves decreased with an increasing deformation temperature at a constant strain rate. Globular and elongated grains in the TiNbTaVW alloy at 950°C and 1000°C confirmed that dynamic globularisation and dynamic recovery are the softening mechanisms. At 1050°C, globular iv grains indicated dynamic globularisation as the softening mechanism. In IN718, equiaxed and elongated grains at 950°C and 1050°C suggested both dynamic recrystallisation and dynamic recovery as the softening mechanisms. At 1000°C, the dominance of equiaxed grains signified dynamic recrystallisation as the only softening mechanism. The TiNbTaVW RHEA has higher temperature strengths of 910 MPa, 870 MPa, and 658 MPa, compared to the IN718 alloy, with 72 MPa, 87 MPa, and 61 MPa at 950°C/10-3 s-1, 1000°C/10-3 s-1, and 1050°C/10-3 s-1, respectively. The higher temperature strength of the TiNbTaVW RHEA can be attributed to both solid solution strengthening and grain boundary strengthening. The TiNbTaVW and CrNbTaVW RHEAs have superior hardness, corrosion resistance and high temperature strength than the IN718 alloy. However, the IN718 alloy has better oxidation resistance than TiNbTaVW and CrNbTaVW. Improving the oxidation resistance of the RHEAs is important for establishing them as leading high-temperature materials. Achieving a balance between the high-temperature properties of RHEAs could develop their application in high-temperature environments, offering more material options for advanced engineering.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Engineering, in the Faculty of Engineering and the Built Environment, SSchool of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Refractory high entropy alloy; Structural applications; Softening mechanism; High- temperature oxidation; Corrosion behaviour; SDG-9: Industry, innovation and infrastructure; SDG-7: Affordable and clean energy